4 - x = 8 - 3x

4 - x = 8 - 3x -x + 3x = 8 - 4 2x = 4 x = 4/2 x = 2

Question

Asked 9/26/2010 3:47:21 PM

Updated 1/11/2018 9:54:30 PM

1 Answer/Comment

Edited by Masamune [1/11/2018 9:54:17 PM]

g
googletag.cmd.push(function() { googletag.display('div-gpt-ad-1564665647093-0'); });

Rating

8

4 - x = 8 - 3x

-x + 3x = 8 - 4

2x = 4

x = 4/2

x = 2

-x + 3x = 8 - 4

2x = 4

x = 4/2

x = 2

Added 1/11/2018 9:54:30 PM

This answer has been confirmed as correct and helpful.

X+5=3X-2

Question

Expert Answered

Updated 6/24/2014 7:54:06 AM

2 Answers/Comments

X + 5 = 3X - 2;

X - 3X = -2 - 5;

-2X = -7;

X = 7/2

X - 3X = -2 - 5;

-2X = -7;

X = 7/2

Added 6/24/2014 7:52:53 AM

This answer has been confirmed as correct and helpful.

2A + 3 = 4 - 3A;

2A + 3A = 4 - 3;

5A = 1;

A = 1/5

2A + 3A = 4 - 3;

5A = 1;

A = 1/5

Added 6/24/2014 7:54:06 AM

This answer has been confirmed as correct and helpful.

3-2X=8X-7

3 - 2X = 8X - 7;

-2X - 8X = -7 + 3;

-10X = -10;

X = 1

Question

Updated 6/24/2014 7:47:13 AM

3 Answers/Comments

3 - 2X = 8X - 7;

-2X - 8X = -7 + 3;

-10X = -10;

X = 1

Added 6/24/2014 7:45:46 AM

This answer has been confirmed as correct and helpful.

3Y + 2 = 7 - 2Y;

3Y + 2Y = 7 - 2;

5Y = 5;

Y = 5/5;

Y = 1

3Y + 2Y = 7 - 2;

5Y = 5;

Y = 5/5;

Y = 1

Added 6/24/2014 7:46:36 AM

This answer has been confirmed as correct and helpful.

4 - X = 8 - 3X;

-X + 3X = 8 - 4;

2X = 4;

X = 4/2;

X = 2

-X + 3X = 8 - 4;

2X = 4;

X = 4/2;

X = 2

Added 6/24/2014 7:47:11 AM

This answer has been confirmed as correct and helpful.

34,014,156

questions answered

There are no comments.